Development of EEG connectivity from preschool to school-age children - Kang, Jiannan; Mao, Wenqin; Wu, Juanmei; Huang, Xinping; Casanova, Manuel F.; Sokhadze, Estate M.; Li, Xiaoli; Geng, Xinling (Frontiers in Neuroscience, 2024)
Introduction Many studies have collected normative developmental EEG data to better understand brain function in early life and associated changes during both aging and pathology. Higher cognitive functions of the brain do not normally stem from the workings of a single brain region that works but, rather, on the interaction between different brain regions. In this regard studying the connectivity between brain regions is of great importance towards understanding higher cognitive functions and its underlying mechanisms. Methods In this study, EEG data of children (N = 253; 3-10 years old; 113 females, 140 males) from pre-school to schoolage was collected, and the weighted phase delay index and directed transfer function method was used to find the electrophysiological indicators of both functional connectivity and effective connectivity. A general linear model was built between the indicators and age, and the change trend of electrophysiological indicators analyzed for age. Results The results showed an age trend for the functional and effective connectivity of the brain of children. Discussion The results are of importance in understanding normative brain development and in defining those conditions that deviate from typical growth trajectories.